Hymeglusin Enhances the Pro-Apoptotic Effects of Venetoclax in Acute Myeloid Leukemia - Zhou, Cheng; Wang, Zhiqin; Yang, Shuanghui; Li, Huan; Zhao, Liang (Frontiers in Oncology, 2022)
Venetoclax is used for the priority treatment of elderly patients with acute myeloid leukemia (AML). Resistance or intolerance to venetoclax offsets its clinical benefits in some patients. Combination strategies with other drugs are promising alternatives to overcome the current complications associated with venetoclax use. Hymeglusin, a specific inhibitor of 3-hydroxy-3-methylglutaryl coenzyme A synthase 1 (HMGCS1), regulates the mevalonate pathway, which is vital for AML growth and chemosensitivity. The effects of the combination of venetoclax and hymeglusin on AML were explored in this study. The correlations between HMGCS1 and apoptosis-related genes were analyzed using the Gene Expression Profiling Interactive Analysis 2 and The Cancer Genome Atlas databases. Apoptosis and cell viability were detected in HL-60 and KG-1 cells after treatment with gradient concentrations of venetoclax or hymeglusin. The transcriptomic profiles of HL-60 and KG-1 cells were compared via RNA-Seq analysis. The effects of venetoclax and hymeglusin on apoptosis were validated in primary cells. The results showed that HMGCS1 expression was closely associated with apoptosis-related genes based on the data from large clinical databases. B cell lymphoma (BCL)-2 expression was elevated in AML and negatively associated with overall survival. Hymeglusin decreased BCL2 expression levels in HL-60 and KG-1 cells. Venetoclax and hymeglusin inhibited cell viability in both cell lines, but induced apoptosis in HL-60 cells. This discrepancy in sensitivity to hymeglusin may be attributed to the positive increase in the expression levels of HMGCS1 and multiple upregulated pro-leukemia genes in KG-1 cells. Combination treatment with venetoclax and hymeglusin significantly increased the apoptotic rates compared to single-agent treatment in both AML cell lines and primary AML cells. Furthermore, the combination strategy did not result in remarkably enhanced toxicity in normal mononuclear cells. Collectively, hymeglusin enhanced the effects of venetoclax on apoptosis. This combination strategy showed enhanced antileukemic activity with acceptable toxicity in AML.